Legal Certainty In The Implementation of Judicial Review Decisions By The Constitutional Court In Indonesia - Joi Phiau, Bun; Rifai, Amzulian; Latif, Abdul (Pelopor Publikasi Akademika, 2025)
This study aims to analyze the implementation of Constitutional Court decisions in Indonesia, particularly focusing on the gap between the legal force of such decisions and their actual enforcement. Despite the Constitutional Court's decisions being final and binding, many are not implemented in accordance with the principle of erga omnes, leading to legal uncertainty and hindering the achievement of justice. This research employs a normative juridical approach, utilizing the theory of the state of law, the constitution, and legal certainty as analytical tools. The study's findings indicate that while Constitutional Court decisions have permanent legal force and should be binding on all parties, inconsistent implementation by institutions such as the House of Representatives and the President remains a significant issue. The primary cause of non-compliance is often the lack of adequate legislative responses or the absence of clear implementing regulations. Furthermore, the study highlights that an ideal implementation of Constitutional Court decisions would require stronger monitoring mechanisms and sanctions to ensure compliance. In conclusion, this study recommends revising relevant laws and regulations and establishing more detailed implementation procedures to support the effective execution of Constitutional Court decisions, ensuring legal certainty, justice, and public trust in the legal system.